Protective effect of angulated aorta for saving coronary artery during endovascular repair for ascending aortic pseudoaneurysm - Kim, Myeong Gun; Kang, Woong Chol; Oh, Pyung Chun; Jeon, Yang Bin; Lee, Ji Yeon; Shin, Eak Kyun (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
Ascending aortic pseudoaneurysm is a rare complication after cardiothoracic surgery and the open surgical repair for this complication is challenging. We report on a patient who developed an ascending aortic pseudoaneurysm after aortic valve replacement (AVR), which was treated successfully with endovascular therapy. Our case showed that angulation of the ascending aorta is one of factors for consideration in application of endovascular therapy and endovascular therapy might be an option for management of ascending aortic pathology in patients with high surgical risk, particularly patients with a severely angulated proximal ascending aorta.